PENGARUH EFIKASI DIRI TERHADAP MOTIF BERWIRAUSAHA SISWA SMK NUSANTARA INDAH SINTANG - Anna Marganingsih (STKIP Persada Khatulistiwa Sintang, 2021)
Today's economic developments open access to global markets as opportunities as well as threats that must be faced with the readiness of competitive human resources. In fact, there are still many open unemployed and underemployed people from elementary school, junior high school and high school /vocational school. Students as immature beings still have to be helped, assisted, guided, trained, and directed to be able to develop their potential optimally, especially in increasing their self-efficacy and being able to become independent as one of the entrepreneurs. This study aims to determine the effect of Self-Efficacy on Entrepreneurial Motives for SMK Nusantara Indah Sintang students. The method used is a quantitative method. The population as well as the sample in this study amounted to 85 people. The data collection tool used is a questionnaire. The results showed that there was a positive and significant effect of self-efficacy on the Entrepreneurial Motives of SMK Nusantara Indah Sintang students. Evidenced by the value of the hypothesis test t arithmetic 8.740 > t table 1.667 means Ho is rejected and Ha is accepted.